EDUKASI KAKI SEHAT DENGAN SPA MENINGKATKAN KEMAMPUAN PENCEGAHAN LUKA KAKI DIABETESI DI UPTD PUSKESMAS PENINJAUAN KABUPATEN OKU - Rustiati, Nelly; Sujati, Ni Ketut; Supangat, Supangat; Khoiriyah, Ina Yatul; Akbar, M. Agung (Nindikayla Institute, 2023)
Diabetic foot wound is a serious complication that has the potential to cause infection, gangrene, and even amputation of the lower extremities. One of the factors that contribute to the occurrence of diabetic foot ulcers is the lack of understanding and awareness about the importance of maintaining healthy feet. Regular foot spa can reduce diabetic foot disease. The purpose of this community service is to increase the community's independence in doing foot spas through the establishment of a healthy foot community. This community service is a Community Empowerment scheme with an Education method through a community of fostered partners, namely Diabetic Groups who meet pre-diabetes and diabetes criteria who are at risk of developing Diabetic foot sores. who are combined in the community of foot fighters as many as 35 people. Foot care ability was observed through a log book sent via Google form. Results: Community service activities under the Community Partnership Program scheme with the target audience for diabetes in the working area of the Review Health Center can increase knowledge of prevention of diabetic complications and be skilled at doing foot spas in everyday life at home. Education participants actively ask questions and take part in re-demonstrations of the Foot Spa training. Positive response from Health Officers and Cadres in participating in all Community Service activities